Impact of EU taxation systems on 1998-2004 economic growth - Kocia, Agata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
This article presents a review of theoretical and empirical tax competition and institutional competition as a basis for constructing and testing an original endogeneous growth model. The corporate and personal tax systems in the European Union members are very different and complex. For many),cars they have motivated countries to modify their systems and offer incentives, e.g. lower tax rates and tax breaks for creating jobs to attract businesses in order to improve economic growth. hi turn, these processes have attracted die attention of government officials, politicians and researchers to study their impact oil growth, among them, Tiebout ( 1956), Brennan and Buchanan (1980), Zodrow and Mieszkowski ( 1986) and North ( 1992). Their work provided conflicting results, while empirical studies increased ambiguity. The author of this work hopes to add another dimension to that literature, with an empirical model providing additional support for positive effects of tax competition and institutional tax variety among EU members on their economic growth
Argumenta Oeconomica, 2008, No 2 (21), s. 5-26
Keywords: tax competition; Tiebout; Leviathan hypothesis; Zodrow-Mieszkowski model; wzrost gospodarczy; konkurencyjność podatkowa; system podatkowy